Good Governance and the Role of the Hospital in Health Worker Education in Africa - Beciu, H. (2012)
This article reviews the need to strengthen good governance in hospitals for them to contribute effectively to production of adequate numbers of quality health workers in the Africa region. It examines this in the context of the global crisis in human resources for health (HRH) and the challenges that confront the Africa region in meeting HRH standards. Using governance models for health educational institutions, the article recommends a shift to a hospital management system with a governance structure that would address not only service delivery but also human resource development.